Atom Dingin dan Penggunaannya (Jurnal Pilar Sains, 2006)
Cooling and Trapping neutral particles or ions using laser beam becomes a new research field inPhysics. This field was started in 1970’s by Ashkin who demonstrated that a focused laser beam ondielectric particles in a glass cell can attract the particles to the focal area because the potenstialenergy there is lower. Cooling which means to reduce the average thermal velocity of atoms orparticles and trapping which means controlling the positions of the atoms can be performed using twokinds of forces from Laser beam i.e. scattering force and gradient force. A scattering force is resultedfrom the laser beam because the laser beam contains fotons which have momentum. The gradientforce appears because of the gradient of intensity around focal area. One of famous atom traps isMagneto-Optical Trap (MOT). MOT uses Doppler effect for cooling and Zeeman effect for trappingWith this technique, cold atoms with temperature in the order of mikro Kelvin can be produced. Coldatom can be used for many applications such as to make Bose Einstein Condensate (BEC), atominterfermetry and atomic clocks.